THE INFLUENCE OF SERVICE QUALITY OF TIRTA BUMI WIBAWA REGIONAL DRINKING WATER COMPANY TOWARDS CUSTOMER SATISFACTION - Anwar, Anisa; Rachmawati, Ike; Nur, Tuah (Jurnal Governansi, 2023)
The research is entitled "The Influence of Service Quality of Tirta Bumi Wibawa Regional Drinking Water Company towards Customer Satisfaction in Sukabumi City". The research was aimed at determining the partial influence of variable (X) Service Quality towards variable (Y) Customer Satisfaction. The research method used was associative method with quantitative approach. The techniques of collecting data applied were in the form of distributing questionnaires and interviews. The research sample used random sampling technique by applying the Slovin formula withaa precision levellof 10%, so that the numberoof samples obtained was 100 respondents from a population of 11,178 people. In order to measure the variable of service quality, researchers used the theory of Parasuraman, et al (1988:12-40) including the dimensions of Tangibles (Direct Evidence), Reliability, Responsiveness, Assurance, and Empathy. Meanwhile, in order to measure the customer satisfaction variable, the theory of Irawan (2008:39) that included the dimensions of Product Quality and Price, was applied. Based on the results of statistical calculations obtained, the results of the influence of service quality towards customer satisfaction is equal to 86.2%, while the remaining 13.8% is influenced by other factors not examined.